Non-receptor Type PTPases and their Role in Controlling Pathways Related to Diabetes and Liver Cancer Signalling - Chaudhary, Nidhee; Kiranmayee, Bellam (Current Pharmaceutical Biotechnology, 2025)
The role of non-receptor type Protein Tyrosine Phosphatase (PTPases) in controlling pathways related to diabetes and Hepatocellular Carcinoma (HCC) is significant. The insulin signal transduction pathway is regulated by the steady-state phosphorylation of tyrosyl residues of the insulin receptor and post-receptor substrates. PTPase has been shown to have a physiological role in the regulation of reversible tyrosine phosphorylation. There are several non-receptor type PTPases. PTPase containing the SH-2 domain (SHP-2) and the non-receptor type PTPase (PTP1B; encoded by the PTPN1 gene) are involved in negative regulation of the insulin signaling pathway, thereby indicating that the pathway can be made more efficient by the reduction in the activity of specific PTPases. Reduction in insulin resistance may be achieved by drugs targeting these specific enzymes. The modifications in the receptor and post-receptor events of insulin signal transduction give rise to insulin resistance, and a link between insulin-resistant states and HCC has been established. The cancer cells thrive on higher levels of energy and their growth gets encouraged since insulin-resistant states lead to greater glucose levels. Cancer, hyperglycemia, and hypoglycemia are highly linked through various pathways hence, clarifying the molecular mechanisms through which non-receptor type PTPase regulates the insulin signal transduction is necessary to find an effective target for cancer. Targeting the pathways related to PTPases; both receptor and non-receptor types, may lead to an effective candidate to fight against diabetes and HCC.
Keywords: Cancer